Characterization of Arabidopsis thaliana Promoter Bidirectionality and Antisense RNAs by Inactivation of Nuclear RNA Decay Pathways. Issue 6 (25th March 2020) - Thieffry, Axel; Vigh, Maria Louisa; Bornholdt, Jette; Ivanov, Maxim; Brodersen, Peter; Sandelin, Albin
Abstract : We report the existence of bidirectionally transcribed loci producing exosome-sensitive RNAs in Arabidopsis in which the produced RNAs are sources of small interfering RNAs, and exosome-sensitive transcripts antisense to genes encoding regulatory proteins, in particular transcription factors. Abstract: In animals, RNA polymerase II initiates transcription bidirectionally from gene promoters to produce pre-mRNAs on the forward strand and promoter upstream transcripts (PROMPTs) on the reverse strand. PROMPTs are degraded by the nuclear exosome. Previous studies based on nascent RNA approaches concluded that Arabidopsis ( Arabidopsis thaliana ) does not produce PROMPTs. Here, we used steady-state RNA sequencing in mutants defective in nuclear RNA decay including the exosome to reassess the existence of Arabidopsis PROMPTs. While they are rare, we identified ~100 cases of exosome-sensitive PROMPTs in Arabidopsis. Such PROMPTs are sources of small interfering RNAs in exosome-deficient mutants, perhaps explaining why plants have evolved mechanisms to suppress PROMPTs. In addition, we found ~200 long, unspliced and exosome-sensitive antisense RNAs that arise from transcription start sites within parts of the genome encoding 3′-untranslated regions on the sense strand. The previously characterized noncoding RNA that regulates expression of the key seed dormancy regulator, DELAY OF GERMINATION1, is a typical representative of this class of RNAs. Transcription factor genes are overrepresented among loci with exosome-sensitive antisense RNAs, suggesting a potential for widespread control of gene expression via this class of noncoding RNAs. Lastly, we assess the use of alternative promoters in Arabidopsis and compare the accuracy of existing TSS annotations.